Meaning, Context and Methodology - Conrad, Sarah-Jane; Petrus, Klaus (De Gruyter Mouton, 2017)
What methodological impact does Contextualism have on the philosophy of language? This collection sets out to provide some answers. The authors in this volume question three ultimately connected assumptions of the philosophy of language. The first assumpt
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Okt 2017)
Keywords: Context Thesis; Contextualism; Philosophy of Language; Pragmatik; Sprachgebrauch; Bedeutung; Aufsatzsammlung